METODE PENGEMBANGAN KECERDASAN SPIRITUAL ANAK USIA DINI TELAAH PEMIKIRAN ABDULLAH NASHIH ULWAN - Ilham Putri Handayani; Deny Irawan (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
Most parents in educating their children only meet the needs of clothing, food, boards and the form of intelligent children in reason and mind. Even though in living this live it is not enough just to do this, parents need to form chidren to have noble character ans spiritually intelligent so that the child is not lonely and has clear golas and directions in life. The main problem in this paper is how the method used by Abdullah Nashih Ulwan in developing early childhood spiritual intelligence is examined from the point of view of Psychology and Islam. This writing uses bibliographic research methods and in analyzing data the autors use documentation techniques to obtain relevant data. The result of this study indicate that the methods used by Abdullah Nashih Ulwan in developing early childhood spiritual intelligence are: 1) the exemplary method. 2) story method. 3) habituation method. 4) advice method. 5) attention and supervision methods. 6) the method of punishment. The six methods when studied from the point of view of Islam and Psycology will greatly help parents to develop their children’s spiritual intelligence from an early age.